Beginners' Greek - Matsukas, Aristarhos (Teach yourself books., 2025)
"Love, Travel, Study, Work, Friendship--whatever your reason for wanting to learn, Beginners' Greek will help you to: Communicate naturally in everyday situations; Build your confidence with easy-to-follow explanations and plenty of practice activities; Understand and pronounce Greek easily with online audio; Become familiar with the Greek alphabet; Remember what you learn with our effective Discovery Method; Focus your learning and track your progress with practical tools and planners."--Page 4 of cover.